Do ABO Blood Group Antigens Hamper the Therapeutic Efficacy of Mesenchymal Stromal Cells? - Moll, Guido (Public Library of Science, 2014)
Investigation into predictors for treatment outcome is essential to improve the clinical efficacy of therapeutic multipotent mesenchymal stromal cells (MSCs). We therefore studied the possible harmful impact of immunogenic ABO blood groups antigens – genetically governed antigenic determinants – at all given steps of MSC-therapy, from cell isolation and preparation for clinical use, to final recipient outcome. We found that clinical MSCs do not inherently express or upregulate ABO blood group antigens after inflammatory challenge or in vitro differentiation. Although antigen adsorption from standard culture supplements was minimal, MSCs adsorbed small quantities of ABO antigen from fresh human AB plasma (ABP), dependent on antigen concentration and adsorption time. Compared to cells washed in non-immunogenic human serum albumin (HSA), MSCs washed with ABP elicited stronger blood responses after exposure to blood from healthy O donors in vitro, containing high titers of ABO antibodies. Clinical evaluation of hematopoietic stem cell transplant (HSCT) recipients found only very low titers of anti-A/B agglutination in these strongly immunocompromised patients at the time of MSC treatment. Patient analysis revealed a trend for lower clinical response in blood group O recipients treated with ABP-exposed MSC products, but not with HSA-exposed products. We conclude, that clinical grade MSCs are ABO-neutral, but the ABP used for washing and infusion of MSCs can contaminate the cells with immunogenic ABO substance and should therefore be substituted by non-immunogenic HSA, particularly when cells are given to immunocompentent individuals.